Pemberdayaan Kelompok Teman Sebaya: Edukasi Penggunaan Terapi Komplementer Untuk Mengurangi Dismenorea Primer - Maringga, Estin Gita; Ivantarina, Dintya (Universitas Nusantara PGRI Kediri, 2023)
Primary dysmenorrhea is an uncomfortable sensation centered in the lower abdomen. One of the therapies to overcome primary dysmenorrhea is complementary therapy. The results of the initial survey at MAN 4 Kediri obtained information that most experienced primary dysmenorrhea with mild to severe pain intensity and lack of information from health workers regarding the use of complementary therapies to reduce primary dysmenorrhea. The purpose of this community service activity is to form a peer group at MAN 4 Kediri in order to provide education and early treatment to young women who experience primary dysmenorrhea. The stages of implementing the activities include: the formation of a peer group; health education about the concept of dysmenorrhea and its management as well as demonstrations of the use of warm compress therapy and relaxation techniques. Evaluation is in the form of knowledge and ability assessment. Follow-up activities in the form of peer group assistance. The results of this activity showed that after being given education about the concept and management of dysmenorrhea, there was an increase in knowledge and being able to practice the use of warm compresses and long breath distraction techniques when experiencing primary dysmenorrhea. This community service activity is expected to empower the group of young women at MAN 4 Kediri to educate their peers about the concept of dysmenorrhea and complementary therapies that are safe for health, effective, and efficient to be applied daily.